EFFECT OF BUFFALO MILK ADDITION ON THE QUALITY OF SWEET CORN FERMENTED BEVERAGE (Zea Mays L.) - Lembong, Elazmanawati; Djali, Mohamad; Lara Utama, Gemilang; Pratiwi Ramadhani, Abbya (Jurnal Teknologi Pertanian, 2026)
Sweet corn based fermented beverages represent a promising innovation in cereal based products with potential as functional foods. However, the low lactose content in corn extract limits the growth of Lactic Acid Bacteria (LAB), thereby necessitating the addition of lactose sources from animal milk. This study aimed to evaluate the effect of buffalo milk addition on the physicochemical, microbiological, and sensory characteristics of a sweet corn based fermented beverage and to determine the optimal formulation. The study employed a completely randomized design with five levels of buffalo milk addition: 0%, 10%, 20%, 30%, and 40%. The parameters analyzed included ash content, protein content, fat content, titratable acidity, total LAB, and sensory properties. The results showed that buffalo milk addition significantly affected all measured parameters. Increasing buffalo milk concentration led to higher ash, protein, fat, titratable acidity, and LAB counts. However, none of the formulations met the minimum protein requirement specified by SNI 2981:2009. The formulation containing 30% buffalo milk was selected as the optimal treatment, as it provided the best balance among physicochemical properties, microbial quality, and sensory acceptability, although it did not yield the highest values for all parameters. The resulting product is more appropriately classified as a corn-based fermented beverage with buffalo milk addition and can be considered to partially meet the requirements of SNI 2981:2009.